2016
DOI: 10.1007/s00170-016-9418-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analyses of helical milling process

Abstract: Abstract:A comparison between the geometry of the helical milling specialized tool and conventional end mill was firstly introduced. Furthermore, a mathematical model, in which the cutting area was divided into different cutting zones, was established to simulate the cutting depths and volume of the different cutting edges (three kinds) on specialized tool. Accordingly, a specific ratio between the volume removed by different edges and the total hole volume was derived mathematically and modeled using 3D model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In this choice, factors such as cost and tool life must also be taken into account. Factors such as the greatest possible versatility of operations, the superior quality of machined surfaces, low cutting forces, and lower operating costs with advantages for productivity demonstrated by HM, appear as strong arguments for this process as an alternative to D. [47][48][49] Isbilir and Ghassemieh 50 developed a FE analysis for D operations in titanium alloys. Zhu et al 51 investigated dry D under different cutting parameters, it was possible to verify that for higher F there is an increase in thrust force, also F greatly influences the size and shape of chips, high V c and low F generates better surface quality than low V c and high F. Waqar et al 52 evaluated the effect of D parameters on hole quality in dry D and concluded that V c is directly responsible for surface quality and better surface finish are obtained with lower F and high V c .…”
Section: Methodsmentioning
confidence: 99%
“…In this choice, factors such as cost and tool life must also be taken into account. Factors such as the greatest possible versatility of operations, the superior quality of machined surfaces, low cutting forces, and lower operating costs with advantages for productivity demonstrated by HM, appear as strong arguments for this process as an alternative to D. [47][48][49] Isbilir and Ghassemieh 50 developed a FE analysis for D operations in titanium alloys. Zhu et al 51 investigated dry D under different cutting parameters, it was possible to verify that for higher F there is an increase in thrust force, also F greatly influences the size and shape of chips, high V c and low F generates better surface quality than low V c and high F. Waqar et al 52 evaluated the effect of D parameters on hole quality in dry D and concluded that V c is directly responsible for surface quality and better surface finish are obtained with lower F and high V c .…”
Section: Methodsmentioning
confidence: 99%
“…Should also be considered in the process of choosing the most adequate method of hole making, the cost of the tools and the task execution time. The tools used in HM were almost 30% of the value of the drills used, with the advantage of flexibility in getting the desired dimension, as was stated by Ozturk et al [27] and Tian et al [21].…”
Section: Discussionmentioning
confidence: 90%
“…Brinksmeier et al [11], Denkena et al [20] and Tian et al [21] analyzed comprehensively the theoretical modelling of HM. In the HM process, the rotating tool, a mill with centre cutting, performs a circular motion in the plane XY simultaneously advancing in Z, thereby describing a vertical downward helical movement.…”
Section: Manufacturing Processesmentioning
confidence: 99%
“…The tooth trajectory is considered circular (cycloid effect neglected), according to Segonds et al [18]. But axial cutting depth b is different to the milling, because axial cutting depth b changes with the position of the side cutting edge [15,19]. As shown in Fig.…”
Section: Instantaneous Cutting Chip Analysis In Helical Millingmentioning
confidence: 99%